Capacitive Organic Anode Based on Fluorinated-Contorted Hexabenzocoronene: Applicable to Lithium-Ion and Sodium-Ion Storage Cells - Park, Jaehyun; Lee, Cheol Woo; Park, Ju Hyun; Joo, Se Hun; Kwak, Sang Kyu; Ahn, Seokhoon; Kang, Seok Ju (WILEY, 2018)
Conducting polymer-based organic electrochemical capacitor materials have attracted attention because of their highly conductive nature and highly reversible redox reactions on the surface of electrodes. However, owing to their poor stabilities in aprotic electrolytes, alternative organic electrochemical capacitive electrodes are being actively sought. Here, fluorine atoms are introduced into contorted hexabenzocoronene (cHBC) to achieve the first small-molecule-based organic capacitive energy-storage cells that operate at high current rates with satisfactory specific capacities of approximate to 160 mA h g(-1) and superior cycle capabilities (>400) without changing significantly. This high capacitive behavior in the P2(1)/c crystal phase of fluorinated cHBC (FcHBC) is caused mainly by the fluorine atoms at the end of each peripheral aromatic ring. Combined Monte Carlo simulations and density functional theory (DFT) calculations show that the most electronegative fluorine atoms accelerate ion diffusion on the surface to promote fast Li+ ion uptake and release by an applied current. Moreover, FcHBC has potential applications as the capacitive anode in Na-ion storage cells. The fast dynamics of its capacitive behavior allow it to deliver a specific capacity of 65 mA h g(-1) at a high current of 4000 mA g(-1).
Keywords: ENERGY-STORAGE; PSEUDOCAPACITOR ELECTRODES; SUPERCAPACITOR; INSERTION; NANOMATERIALS; CHALLENGES; CHARGE; FILMS